Association between maternal psychological distress and children's neurodevelopment in offspring aged 4 years in Japan: The Tohoku Medical Megabank Project Birth and Three‐Generation Cohort Study. (8th February 2023) - Takahashi, Ippei; Obara, Taku; Kikuchi, Saya; Kobayashi, Mika; Ishikuro, Mami; Murakami, Keiko; Ueno, Fumihiko; Noda, Aoi; Onuma, Tomomi; Matsuzaki, Fumiko; Kobayashi, Natsuko; Hamada, Hirotaka; et al.
Abstract : Aim: An association between maternal psychological distress and children's development has been reported, but reports from Japan are limited. This study aimed to examine the association of maternal psychological distress with children's neurodevelopment in Japan. Methods: The study assessed data of 7646 mother–infant pairs in the Japanese population. We used Kessler Psychological Distress Scale, a screening tool for psychological distress, to assess maternal psychological distress in early pregnancy and 2 years postpartum and divided it into four categories: none in both the pre‐natal and post‐natal periods, only the pre‐natal period, only the post‐natal period and both the pre‐natal and post‐natal periods. Children's neurodevelopment was assessed using the Ages & Stages Questionnaires Third Edition (ASQ‐3) at 4 years of age. ASQ‐3 comprises five domains (communication, gross motor, fine motor, problem solving and personal–social), and the score of less than −2 standard deviation relative to the mean in reference was defined as having developmental delay. We conducted multivariate logistic regression analysis to examine the association between maternal psychological distress and children's neurodevelopment. Results: The prevalence of developmental delay of communication, gross motor, fine motor, problem solving and personal–social were 4.0%, 4.3%, 4.9%, 3.8% and 4.6%, respectively. Maternal psychological distress in only the postpartum period and both pre‐natal and postpartum periods were associated with risks of developmental delay in all domains. Maternal psychological distress in only the pre‐natal period was associated with developmental delay in communication. Conclusions: Maternal psychological distress is associated with risks of children's developmental delay.